Evaluation of Educational Resource Efficiency Based on the Data Envelopment Analysis Model and Malmquist Index - Ren, Xiaodong; Kongkaew, Tharitsaya (Arts of Management Journal, 2024)
This article aimed to apply the DEA-BCC model and the DEA-Malmquist index to evaluate the efficiency of educational resource allocation in provincial universities. Secondary data were obtained from 40 provincial colleges and universities in Sichuan Province from 2017 to 2022. Factors such as human, physical, and financial capital were used as input indicators, while educational outcomes, scientific research, and social services served as output indicators. The DEA-BCC model shows that the average value of comprehensive technical efficiency was 0.911, with an average pure technical efficiency of 0.978 and an average scale efficiency of 0.929, indicating scale efficiency as a constraining factor. According to the DEA-Malmquist index model results, the total factor productivity has an average value of 0.707. This suggests a 29.30% decrease in efficiency over these 6 years. The average value of the technical efficiency index is 0.985, which decreases by 0.074. The average value of the technological progress efficiency index was 0.718, indicating that the sample of provincial universities did not experience high technological progress efficiency. Technological regression during this period primarily influenced the changes in total factor productivity. The research findings indicate technical efficiency issues in utilizing educational resources at provincial universities. The results of this study are anticipated to offer valuable insights and benefits to key stakeholders in the education sector. By presenting a robust tool for assessing the efficiency of educational resource allocation, the study underscores the critical role of technical and scale efficiencies in enhancing effectiveness. Through a comprehensive analysis of educational resource inputs and outputs, this paper identifies the key factors influencing efficiency, providing invaluable data support to decision-makers and managers in the education sector.